Cost considerations in the management of atrial fibrillation – impact of dronedarone - Khaykin, Yaariv (Dove Medical Press, 2012)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. It is associated with significant morbidity and mortality. At the societal level, AF carries an enormous cost. Strategies aimed at reducing AF morbidity and mortality and containing the associated fiscal burden are of paramount importance. This review will discuss AF treatment strategies and economics, focusing on the impact of dronedarone, a novel antiarrhythmic agent.